Calculating The Philosophical Significance of The Concept of Religious Freedom in Islam - Alim Roswantoro (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
The writing attemps to explore the philosophical meaning of the theological messages of Islam on religious freedom. The article do not study the empirical facts of religious freedom practiced by muslims today, but it scrutinizes the theological messages as written in the Qur’an and as showed by the real examples of the God’s Messenger. Through understanding some Qur’anic verses, we will find that Islam strongly encourages the life of different religious people based on the value of freedom. Freedom intended to be a base of religious life is not freedom to do whatever someone wants, but freedom to respect and to protect one another among religious people who are different in religion and faith. This value of message of religious freedom was wonderfully performed in historical practices of the Prophet Muhammad puh. From the Islamic principles of religious freedom that can be underlined, the writing finally tries to elucidate its philosophical meaning. The messages of religious freedom in Islam contain the strong and deep philosophical meaning, because the establishment of religious freedom is based on the fundamental value of human freedom and on the freedom as the nature of life itself.